Hire Purpose : How Smart Companies Can Close the Skills Gap - Mulligan, Deanna; Byron, Auguste; Shaw, Greg (New York, NY : Columbia University Press, 2020)
Automation is no longer a hobbyhorse of futurists, but a pressing concern for the current generation of leaders in both the private and public sectors. In the next ten to fifteen years, work and life at every level of society are going to be transformed. Emerging technology will revolutionize nearly every job, eliminate some, and create new forms of work that we have yet to imagine. How can we survive and thrive in the face of drastic change?Deanna Mulligan offers a practical, broad-minded look at the effects of automation and why the private sector needs to lead the charge in shaping a values-based response. With a focus on the power of education, Mulligan proposes that the solutions to workforce upheaval lie in reskilling and retraining for individuals and companies adapting to rapid change. By creating lifelong learning opportunities that break down boundaries between the classroom and the workplace, businesses can foster personal and career well-being and growth for their employees. Drawing on her own experiences, historical examples, and reports from the frontiers where these issues are unfolding, Mulligan details how business leaders can prepare for and respond to technological disruption. Providing a framework for concrete and meaningful action, Hire Purpose is an essential read about the transformations that will shape the next decade and beyond.
Frontmatter -- Contents -- Foreword -- Introduction -- I. Insurance -- 1. Transforming an Incumbent Industry -- II. Education and Training -- 2. The Future of Work Is Happening Now -- 3. All Together Now: Aligning Education and Training for the Future -- 4. Bring the Classroom Into the Workplace -- 5. Bring the Workplace Into the Classroom -- 6. Reimagine the Diploma -- 7. Put People First -- III. The Role of Business and Industry -- 8. Trust in Purpose -- 9. Conclusion -- Acknowledgments -- Appendix -- Notes -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 06. Jan 2021)
Keywords: Automation -- Economic aspects; Business; Employees -- Effect of automation on; Social responsibility of business; BUSINESS & ECONOMICS / Management